Elevated body roundness index increases the risk of cardiovascular disease in Chinese patients with circadian syndrome - Zhang, Fenglin; Shi, Wenhua; Wen, Jingwei; Cao, Haiming; Xu, Wenjing; Lan, Taohua; Jiang, Wei; Chen, Xiankun; Lu, Weihui (Frontiers in Endocrinology, 2025)
ObjectiveThe body roundness index (BRI) and circadian syndrome (CircS) are considered new risk factors for cardiovascular disease (CVD), yet it remains uncertain whether elevated BRI is associated with CVD incidence in CircS patients. In this study, we investigated the association between BRI and CVD occurrence among CircS participants.MethodsWe conducted a retrospective cohort study involving 8,888 participants aged ≥45 years from the China Health and Retirement Longitudinal Study (CHARLS 2011-2020 wave). CircS was evaluated with a combination of the International Diabetes Federation (IDF) MetS, along with short sleep duration and depression. The threshold for CircS was established at ≥4. In the first phase, the receiver operating characteristic (ROC) curves were used to evaluate the accuracy of diagnosing CircS according to baseline BRI. During the 9-year follow-up, the associations between BRI and CVD incidence in CircS patients were explored by employing logistic regression, restricted cubic spline (RCS) analysis, and subgroup analysis.ResultsBRI demonstrated an independent association with CircS, and multivariable-adjusted restricted cubic spline analyses suggested “J-shaped” associations between BRI and risk of CircS. BRI demonstrated better diagnostic performance in diagnosing CircS compared to general obesity indices such as ABSI (AUC: 0.617), BMI (AUC: 0.746), and WC (AUC: 0.722), with an AUC of 0.760. After a 9-year follow-up, BRI was found to be independently associated with the occurrence of CVD in CircS patients, and the associations between incident CVD and the second, third, and fourth BRI quartiles were 1.30 (95% CI: 0.99~1.69), 1.32 (95% CI: 1.01~1.72), and 1.59 (95% CI: 1.21~2.08), respectively, relative to the first BRI quartile. Then, we assessed the relationship between other obesity indices and the CVD occurrence, and likewise observed a significant effect in the fourth quartile.ConclusionBRI was independently associated with CircS, outperforming obesity indices such as BMI and WC in identifying individuals with CircS. During the 9-year follow-up, elevated BRI levels was significantly associated with CVD incidence among CircS patients, especially in men. Thus, early identification of high-risk populations with CircS and elevated BRI levels may help promote healthy aging among middle-aged and elderly individuals.